Relevansi Nilai Dasar Bela Negara Dengan Pembayaran Zakat dan Implikasinya Terhadap Ketahanan Pribadi - ADE NUR ROHIM (Jurnal Ketahanan Nasional, 2020)
ABSTRACT This article aimed to examined the relevance of the basic values of state defense with the activity of paying zakat, so that the approach taken was ideological, which had implications for the realization of personal resilience. The research used a qualitative method through descriptive content and literature study. The data analyzing process used were collecting data, reducing data, presenting data, and drawing conclusion.The results of the study showed that zakat beside that it was an obligation and pillar of Islam for every Muslim, it was also an activity that implemented the basic values of state defense and internalizing them into the attitudes and behavior of those who payed zakat. The values that were implemented include loving the country, being aware of the nation and state, believing in Pancasila as the state ideology, being willing to sacrificed for the nation and state, and having the initial ability to defended the state. Thus, the value relevance and wisdom contained in zakat on the basic value of defending the country had a positive impact on the formation of the personal resilience of those who payed zakat. The behavior of paying zakat directly fostered a patriotic spirit and loved for the motherland in him and strengthened his belief in Pancasila, which was the nation's ideology and contributed to increased self-sacrifice for the benefit of religion and the nation.ABSTRAK Artikel ini bertujuan untuk mengkaji relevansi nilai-nilai dasar bela negara dengan aktivitas membayar zakat, sehingga pendekatan yang dilakukan bersifat ideologis yang berimplikasi pada perwujudan ketahanan pribadi.Metode penelitian yang digunakan adalah metode kualitatif melalui pendekatan deskriptif dan studi pustaka. Proses analisis data dilakukan dengan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan.Hasil kajian menunjukkan bahwa zakat selain menjadi kewajiban dan rukun Islam bagi setiap muslim, ia juga merupakan aktivitas yang mengimplementasikan nilai-nilai dasar bela negara dan menginternalisasikannya ke dalam sikap dan perilaku orang yang membayar zakat. Nilai-nilai yang diimplementasikan antara lain cinta tanah air, sadar berbangsa dan bernegara, yakin pada Pancasila sebagai ideologi negara, rela berkorban untuk bangsa dan negara, serta memiliki kemampuan awal bela negara. Dengan demikian, relevansi nilai dan hikmah yang terkandung di dalam zakat terhadap nilai dasar bela negara memberikan dampak positif terhadap pembentukan ketahanan pribadi orang yang membayarkan zakat. Perilaku membayar zakat tersebut secara langsung menumbuhkan jiwa patriot dan cinta tanah air dalam dirinya, serta meneguhkan keyakinannya terhadap Pancasila yang merupakan ideologi bangsa, dan turut meningkatkan sikap rela berkorban untuk kepentingan agama dan bangsa.